Précisions au sujet des termes de débit, d’écoulement et de ruissellement en hydrologie - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
Hydrology, one of the most neglected branches of geography, is primarily the study of flowing waters derived from precipitations. Hence, the words « discharge » , «  flow » and « run-off » are at the core of research in this field. There is much confusion about these terms which are not given the same meanings by the various authors. The best definitions would be the following : « discharge » means the quantity of water that flows ; « flow » concerns rather the action of flowing, and « run-off » is the part of the rainfall that flows, or the quantity of rainfall using streams when leaving a region. The epithets added to these basic terms are also very different from one researcher to another or from one country to another. Trying to eliminate this looseness of terminology, the author bas attempted to define the main qualificatives applied to the three fundamental words. Hence the hydrological studies will gain in accuracy. French and English terms used in scientific publications should be as much equivalent as possible.